The Fungal Development During The Leaf Litter Process Decomposition of Avicennia marina - Yunasfi; Nurul Rakesya; Afifuddin Dalimunthe (Journal of Sylva Indonesiana, 2024)
The existence of mangrove ecosystems decreases from land conversion into residential areas, industries, plantations, road facilities and the construction of ponds. This research was conducted in the mangrove forest area of Secanang Belawan Village, Medan, at the Biotechnology Laboratory of the Department of Forestry, Faculty of Agriculture, USU and at the Microbiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, USU Medan. The study's objective was to identify the different fungal species that were present at 10 ppt salinity levels, 10–20 ppt, and 20–30 ppt as well as the pace at which Avicennia marina leaf litter. The research method used litter bags filled with leaf litter of Avicennia marina (50 g) with 7 treatments, 3 replications and 3 levels of salinity. The A. marina leaf litter that had a salt level of 10 ppt had the highest level of decomposition. The dry weight of leaf litter left in the litter bag, which is 4.92 g on average. The largest dry weight of the remaining litter was found in an environment with a salinity of 20 – 30 ppt, which is an average of 10.42 g. The rate of decomposition of A. marina leaf litter in an environment with a salt level greater than 30 ppt is 6.53/yr (or almost equal to residence period of = 0.15 yr). The number of fungal species discovered in the leaf litter of A. marina, which goes through a breakdown process at salinity levels between 0 and 10 ppt and contains 9 species, is another way to observe the impact of salt level. In comparison to the large at salinity levels of 10 to 20 ppt and 20 to 30 ppt, respectively, there were populations of fungus that underwent the process of decomposition in A. marina leaf litter, with an average of 5.99 x 102 cfu/ml and 5.5 x 102 cfu/ml, the fungal population that was the highest concentration was 10.72 x 102 cfu/ml